2001
DOI: 10.1152/ajprenal.2001.280.5.f838
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase plays an essential role in regulation of renal oxygen consumption by NO

Abstract: Nitric oxide (NO) regulates renal O2 consumption, but the source of NO mediating this effect is unclear. We explored the effects of renal NO production on O2 consumption using renal cortex from mice deficient (-/-) in endothelial (e) nitric oxide synthase (NOS). O2 consumption was determined polarographically in slices of cortex from control and eNOS-/- mice. NO production was stimulated by bradykinin (BK) or ramiprilat (Ram) in the presence or absence of an NOS inhibitor. Basal O2 consumption was higher in eN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…We have previously shown that NO production by the eNOS isoenzyme in the kidney is responsible for regulation of renal oxygen consumption (25). Whole-body oxygen consumption is increased in SHR, an observation consistent with a decreased effect of NO (26).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…We have previously shown that NO production by the eNOS isoenzyme in the kidney is responsible for regulation of renal oxygen consumption (25). Whole-body oxygen consumption is increased in SHR, an observation consistent with a decreased effect of NO (26).…”
supporting
confidence: 56%
“…*, P Ͻ 0.05 versus WKY rats in the presence of L-NAME and SHR rats in the absence of L-NAME. ously reported in normal mice and dogs (25,28). In SHR, there was a significant decrease in the response to all three of these stimulators of endogenous NO production, suggesting a defect in renal NO production.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, the site of NO production seems to be of major importance. Stimulation of eNOS by bradykinin increases the inhibition of mitochondrial respiration, supporting the idea of a regulatory role for eNOS (168). Furthermore, Clementi et al (169) found that only cell-secreted NO competes with O 2 and to regulate mitochondrial respiration.…”
Section: Mitochondrial Activity and No-mediated O 2 Consumptionmentioning
confidence: 84%
“…NO has a number of beneficial effects in various systems and importantly functions as a physiological vasodilator in the coronary artery vascular bed, a regulator of mitochondrial respiration, a modulator of myocardial contractility, and a key metabolite in blood pressure regulation (1,30,32,59). Most of the functions for NO in the cardiovascular system are attributable to the enzyme eNOS, which is expressed in the endothelium as well as the cardiomyocyte.…”
Section: Discussionmentioning
confidence: 99%